Definición de los límites operativos para pozos candidatos a ser estimulados con alta presión en el campo Cusiana (2019)
The present work focuses on studying and defining the operational limits of 7 candidate wells to be stimulated with high pressure in the Cusiana field to recover as many reserves as possible in the Mirador formation, since by the primary production focus of the field no this training was taken into account. Initially it investigates geological generalities of the field, it is continued to make a description of the norm for stimulation with high pressure and guides that apply for the safety factors that are used in each situation according to the operator of the field., A brief description of records and by Last simulations in Wellcat to see the status of completion of each well.